WTO and World Trade Challenges in a New Era - Heiduk, Günter S.; Wong, Kar-yiu (Contributions to Economics, 2005)
World trade is not only an economic but also a social, political, environmental, labor and legal matter. Economists and government planners aim at finding the efficient trade policy which enhances economic welfare and growth in a more harmonious and sustainable way. This book contains 12 articles from internationally renowned experts in the field of world trade. The contributions cover a variety of pressing topics related to trade theory, trade policy, WTO and their relationship. They provide in-depth analysis of some of the trade issues currently discussed by academics and politicians, such as resource allocation, income distribution, employment, growth, technology transfer, heterogeneous markets, intra-industry trade as well as environmental issues.